Method for simply and conveniently activating oxidation reduction of oxygen ions of sodium ferrimanganate positive electrode material
By introducing nitric acid in the preparation process of sodium ion battery positive electrode material to provide a strong oxidation environment and increasing the content of Mn4+, the problems of high preparation cost and difficulty in industrial application of sodium ion battery layered metal oxide positive electrode material in the prior art are solved, and the problem of high preparation cost and difficulty in industrial application is achieved. Higher discharge specific capacity performance and lower preparation cost.
Patent Information
- Application Number
- CN202411664481.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing sodium ion battery layered metal oxide cathode material has high preparation cost and is difficult to use in industrial use, resulting in a low discharge specific capacity, which hinders its commercial use.
The method of simple activation of sodium ferromanganate positive electrode material is adopted. By introducing nitric acid during the preparation process, the content of Mn4+ is increased, thereby triggering the oxidation reduction reaction of oxygen ions during the charge and discharge process, and improving the discharge specific capacity of the material.
The sodium ferromanganate positive electrode material prepared by this method has high purity and good crystallinity, which significantly improves the discharge specific capacity performance, and reduces the preparation cost, making it suitable for industrial production applications.
Smart Images

Figure CN119461494A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of positive electrode materials for sodium ion batteries, and in particular relates to a method for simply activating the redox of oxygen ions in a positive electrode material of sodium ferromanganate. Background Art
[0002] Layered metal oxides for sodium-ion batteries are considered to be one of the alternatives to lithium-ion battery cathode materials due to their simple preparation process, good high and low temperature performance, and high cycle stability. However, their low discharge gram-specific capacity seriously hinders their commercial application. Therefore, improving the discharge gram-specific capacity of layered metal oxide cathode materials for sodium-ion batteries is currently a focus of attention.
[0003] At present, a large number of scientific researchers have improved the discharge gram capacity of layered metal oxides by means of doping, coating and constructing high entropy materials. For example, CN118472235A proposed a material that constructs a high entropy structure by doping with a variety of metal ions to improve the energy density of layered metal oxides. The material has a discharge capacity of 130 to 200 mAh / g in the voltage range of 2 to 4 V at a current density of 0.1C, and a capacity retention rate of 99.81% after 100 cycles at a current density of 10C. However, the cost of this material is high due to the introduction of too many metal ions, and it is difficult to prepare it industrially. For example, CN118472235A doped Ru, Ir and Metals with catalytic properties such as Ag are used to introduce strong metal bonds into the material, thereby effectively stabilizing the layered oxide structure and compressing the interplanar spacing of the transition metal layer. Only trace amounts of doping are required to achieve high efficiency, effectively enhancing the stability of the structure and extending the cycle life. However, the introduction of catalytic metals will still increase the preparation cost. For example, CN116143194B uses a unique preparation process to prepare a three-phase symbiotic material of P2, O3 and sodium-rich materials, which exhibits excellent electrochemical properties when used in sodium-ion batteries. However, the preparation of the three-phase symbiotic material is difficult and its industrial application is difficult.
[0004] In summary, the layered metal oxides prepared by the above three methods all have excellent electrochemical properties, but they all have the disadvantages of high cost and difficulty in industrial application. Therefore, how to simply improve the discharge capacity of layered metal oxide positive electrode materials for sodium ion batteries is a problem that needs to be solved. Summary of the invention
[0005] The present invention aims to provide a method for simply activating the redox of oxygen ions in sodium ferromanganate positive electrode materials, so as to solve the problem that the cost of preparing layered metal oxides in the prior art is relatively high and the industrial application is difficult.
[0006] A simple method for activating oxygen ion redox of sodium iron manganese oxide cathode material in this solution, the chemical formula of the sodium iron manganese oxide cathode material is Na x Fe y Mn z O n , where 0.44 < x < 0.8, 0 < y < 1, 0 < z < 1, 1.6 < n < 2.2, and the preparation method includes the following steps:
[0007] S1: Measure deionized water and place it in a beaker. Dissolve the sodium source and the iron manganese metal source according to the molar ratio of each element in the chemical formula in deionized water to obtain a mixed solution;
[0008] S2: Place the beaker containing the mixed solution in S1 in a water bath, stir rapidly, then add concentrated nitric acid to it, and then stir until the solution evaporates and take out the precipitated solid;
[0009] S3: Transfer the solid precipitated in S2 to a blast drying oven and bake it to obtain a dry powder;
[0010] S4: Transfer the dry powder obtained in S3 into a porcelain boat, place the porcelain boat in a tubular furnace, and successively carry out pre-sintering and high-temperature sintering in an air atmosphere, and then take it out after cooling the furnace temperature to room temperature to obtain a sintered product.
[0011] S5: Grind the sintered product in S4 into powder and sieve it to obtain the sodium iron manganese oxide cathode material (Na x Fe y Mn z O n ), where 0.44 < x < 0.8, 0 < y < 1, 0 < z < 1, 1.6 < n < 2.2.
[0012] Furthermore, the sodium source in S1 is one of NaOH, NaCl, CH3COONa, and NaNO3, the iron source is one of Fe(NO3)3·9H2O, FePO4, and C4H6O4Fe, and the manganese source is one of C4H6MnO4, MnCO3, and MnC2O4·2H2O, and the sodium source is in excess of 2-5% in terms of sodium element.
[0013] Furthermore, the heating temperature of the mixed solution in S2 is 60-80 °C, the stirring speed is 200-400 rpm, and then 5-10 ml of concentrated nitric acid with a concentration of 98% is added.
[0014] Furthermore, the temperature of the blast drying oven in S3 is 60-80 °C, and the baking time is 6-8 h.
[0015] Furthermore, the pre-sintering temperature in S4 is 300-400 °C, the heating rate is 2-10 °C / min, and the holding time is 2-4 h.
[0016] Furthermore, the high temperature calcination temperature in S4 is 800-950° C., the holding time is 8-16 h, the heating rate is 2-10° C. / min, and the holding time is 10-16 h.
[0017] Furthermore, the cooling rate in S4 is 2 to 10° C. / min.
[0018] Furthermore, the sieving mesh number in S5 is 100 to 300 meshes.
[0019] The working principle and beneficial effects of this scheme: The sodium ferromanganate positive electrode material prepared by this method has high purity and good crystallinity, and the various elements are evenly distributed. Compared with similar metal layered oxide positive electrode materials, this material exhibits better discharge specific capacity performance. This method introduces nitric acid to provide a strong oxidizing environment, thereby increasing the Mn 4+ The content of , thereby triggering the redox reaction of oxygen ions in the layered metal oxide during the charge and discharge process, significantly improving the discharge specific capacity of the material.
[0020] Traditional preparation methods of sodium ferromanganate positive electrode materials usually rely on catalytic precious metals such as Ru, Ir and Ag to achieve oxygen ion redox reactions. The manufacturing cost is high and it is not suitable for industrial mass production. The present method provides a strong oxidizing environment through nitric acid, which reduces the cost while ensuring the purity and crystallinity of sodium ferromanganate, and has higher feasibility in actual industrial production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a result diagram of an XRD analysis experiment in a method for simply activating the redox of oxygen ions in a sodium ferromanganate positive electrode material of the present invention;
[0022] Figure 2 This is a result diagram of a SEM analysis experiment in a method for simply activating the redox of oxygen ions in a sodium ferromanganate positive electrode material of the present invention;
[0023] Figure 3 This is a result diagram of a charging point test in a method for simply activating the redox of oxygen ions in a sodium ferromanganate positive electrode material of the present invention. DETAILED DESCRIPTION
[0024] Embodiment 1:
[0025] A method for simply activating the redox of oxygen ions in a sodium ferromanganate cathode material comprises the following steps:
[0026] S1: Take 100 ml of deionized water and place it in a beaker. Then add NaNO3, Fe(NO3)3·9H2O and C4H6MnO4 according to the Na0.67 Fe 1 / 2 Mn 1 / 2 The molar ratio of each element in the chemical formula of O2 is dissolved in deionized water to obtain a mixed solution, wherein the sodium source is 5% in excess in terms of sodium element;
[0027] S2: Place the beaker containing the mixed solution in S1 in a magnetic stirring water bath, stir at 80°C and 200 rpm, then add 5 ml of 98% concentrated nitric acid, stir until the solution is completely evaporated, and then take out the precipitated solid;
[0028] S3: The solid precipitated in S2 was transferred to a forced air oven and baked at 60°C for 6 h to obtain a dry powder;
[0029] S4: The dry powder obtained in S3 is transferred to a porcelain boat, and the porcelain boat is placed in a tube furnace. In an air atmosphere, the temperature is increased to 400°C at a heating rate of 2°C / min, and the temperature is kept for 4 hours; then the temperature is increased to 950°C at a heating rate of 2°C / min, and the temperature is kept for 16 hours. Then, the temperature is reduced to room temperature at a cooling rate of 2°C / min, and the sintered product is taken out;
[0030] S5: Take out the sintered product in S4, grind it into powder with a mortar, and pass it through a 200-mesh sieve to obtain the sodium ferromanganate positive electrode material (Na 0.67 Fe 1 / 2 Mn 1 / 2 O2).
[0031] Embodiment 2:
[0032] A method for simply activating the redox of oxygen ions in a sodium ferromanganate cathode material comprises the following steps:
[0033] S1: Take 100 ml of deionized water and place it in a beaker. Then add NaOH, Fe(NO3)3.9H2O, FePO4 and MnC2O4.2H2O according to the Na 0.67 Fe 1 / 2 Mn 1 / 2 The molar ratio of each element in the chemical formula of O2 is dissolved in deionized water to obtain a mixed solution, wherein the sodium source is in excess of 3% in terms of sodium element;
[0034] S2: Place the beaker containing the mixed solution in S1 in a magnetic stirring water bath, stir at 70°C and 300 rpm, then add 5-10 ml of 98% concentrated nitric acid, stir until the solution is completely evaporated, and then take out the precipitated solid;
[0035] S3: The solid precipitated in S2 was transferred to a forced air oven and baked at 80°C for 6 h to obtain a dry powder;
[0036] S4: The dry powder obtained in S3 is transferred to a porcelain boat, and the porcelain boat is placed in a tube furnace. In an air atmosphere, the temperature is increased to 400°C at a heating rate of 10°C / min, and the temperature is kept for 4 hours; then the temperature is increased to 950°C at a heating rate of 10°C / min, and the temperature is kept for 16 hours. Then, the temperature is decreased to room temperature at a cooling rate of 10°C / min, and the sintered product is taken out;
[0037] S5: Take out the sintered product in S4, grind it into powder with a mortar, and pass it through a 200-mesh sieve to obtain the sodium ferromanganate positive electrode material (Na 0.67 Fe 1 / 2 Mn 1 / 2 O2).
[0038] Embodiment 3:
[0039] A method for simply activating the redox of oxygen ions in a sodium ferromanganate cathode material comprises the following steps:
[0040] S1: Take 100ml of deionized water and place it in a beaker. Then mix CH3COONa, FePO4 and C4H6MnO4 according to NaFe 1 / 2Mn 1 / 2 The molar ratio of each element in the chemical formula of O2 is dissolved in deionized water to obtain a mixed solution, wherein the sodium source is in excess of 2% in terms of sodium element;
[0041] S2: Place the beaker containing the mixed solution in S1 in a magnetic stirring water bath, stir at 400 rpm at 80°C, then add 8 ml of 98% concentrated nitric acid, stir until the solution is completely evaporated, and then take out the precipitated solid;
[0042] S3: The solid precipitated in S2 was transferred to a forced air oven and baked at 80°C for 6 h to obtain a dry powder;
[0043] S4: The dry powder obtained in S3 is transferred to a porcelain boat, and the porcelain boat is placed in a tube furnace. In an air atmosphere, the temperature is increased to 400°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours; then the temperature is increased to 950°C at a heating rate of 5°C / min, and the temperature is kept for 16 hours. Then, the temperature is reduced to room temperature at a cooling rate of 5°C / min, and the sintered product is taken out;
[0044] S5: Take out the sintered product in S4, grind it into powder with a mortar, and pass it through a 200-mesh sieve to obtain the sodium ferromanganate positive electrode material (NaFe 1 / 2 Mn 1 / 2 O2).
[0045] The above three embodiments can all easily produce sodium ferromanganate positive electrode materials using the same method by changing some raw materials and ratios. Taking Example 1 as an example, the prepared sodium ferromanganate positive electrode materials are subjected to XRD analysis, SEM analysis and charge and discharge tests.
[0046] XRD analysis experiment:
[0047] XRD analysis Figure 1 As shown in the figure, the diffraction peaks of the prepared sodium ferromanganate positive electrode material can be indexed to P2-Na 0.67 Fe 1 / 2 Mn 1 / 2 O2, all belong to the P / 63mmc space group. The diffraction peaks in the figure are sharp and the peak width is small, indicating that the material has good crystallinity.
[0048] SEM analysis experiment:
[0049] SEM analysis Figure 2 As shown, the material synthesized in Example 1 is a secondary particle with a size of about 40 μm formed by the agglomeration of numerous primary particles with a size of 600-800 nm, and exhibits a distinct layered structure. The primary particles are relatively loosely stacked, so it has good electrochemical properties.
[0050] Charge and discharge test:
[0051] Charging test Figure 3 As shown, the positive electrode material obtained in Example 1 has a first-cycle discharge capacity of 160.56 mAh / g at a 0.1C rate in the voltage range of 2 to 4 V, and its dq / dv curve has a peak at 3.4 V.
[0052] Beneficial effects: The sodium ferromanganate cathode material prepared by this method has high purity and good crystallinity, and the elements are evenly distributed. Compared with similar metal layered oxide cathode materials, this material exhibits better discharge specific capacity performance. This method introduces nitric acid to provide a strong oxidizing environment, thereby increasing the Mn 4+ The content of , thereby triggering the redox reaction of oxygen ions in the layered metal oxide during the charge and discharge process, significantly improving the discharge specific capacity of the material.
[0053] Traditional preparation methods of sodium ferromanganate positive electrode materials usually rely on catalytic precious metals such as Ru, Ir and Ag to achieve oxygen ion redox reactions. The manufacturing cost is high and it is not suitable for industrial mass production. The present method provides a strong oxidizing environment through nitric acid, which reduces the cost while ensuring the purity and crystallinity of sodium ferromanganate, and has higher feasibility in actual industrial production applications.
[0054] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode materials, characterized in that: The chemical formula of the sodium iron manganese oxide cathode material is Na x Fe y Mn z O n , where 0.44 < x < 0.8, 0 < y < 1, 0 < z < 1, 1.6 < n < 2.2, and the preparation method includes the following steps: S1: Deionized water is measured and placed in a beaker, and a sodium source and an iron and manganese metal source are dissolved in the deionized water according to the molar ratio of each element in the chemical formula to obtain a mixed solution; S2: Place the beaker containing the mixed solution in S1 in a water bath, stir rapidly, then add concentrated nitric acid, and stir until the solution evaporates and take out the precipitated solid; S3: The solid precipitated in S2 is transferred to a forced air oven and baked to obtain a dry powder; S4: the dry powder obtained in S3 is transferred into a porcelain boat, the porcelain boat is placed in a tube furnace, and pre-sintered and sintered at high temperature in an air atmosphere, and then taken out after the temperature is cooled to room temperature to obtain a sintered product; S5: The sintered product in S4 was ground into powder using a mortar and sieved to obtain the sodium ferromanganate positive electrode material (Na x Fe y Mn z O n ), of which 0.44 <x<0.8,0<y<1,0<z<1,1.6<n<2.2。 2. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode materials according to claim 1, characterized in that: The sodium source in S1 is one of NaOH, NaCl, CH3COONa and NaNO3, the iron source is one of Fe(NO3)3.9H2O, FePO4 and C4H6O4Fe, and the manganese source is one of C4H6MnO4, MnCO3 and MnC2O4.2H2O, wherein the sodium source is in excess of 2-5% in terms of sodium element.
3. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode material according to claim 2, characterized in that: The mixed solution in S2 is heated to 60-80° C. and stirred at 200-400 rpm, and then 5-10 ml of 98% concentrated nitric acid is added.
4. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode material according to claim 1, characterized in that: The temperature of the S3 blast oven is 60-80° C., and the baking time is 6-8 hours.
5. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode material according to claim 1, characterized in that: The pre-burning temperature in S4 is 300-400° C., the heating rate is 2-10° C. / min, and the holding time is 2-4 hours.
6. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode material according to claim 1, characterized in that: The high temperature calcination temperature in S4 is 800-950° C., the holding time is 8-16 hours, the heating rate is 2-10° C. / min, and the holding time is 10-16 hours.
7. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode materials according to claim 1, characterized in that: The cooling rate in S4 is 2-10°C / min.
8. A method for simply activating the redox of oxygen ions in sodium ferromanganate cathode material according to claim 1, characterized in that: The sieving mesh number in S5 is 100 to 300 meshes.
Citation Information
Patent Citations
A three-phase intergrowth layered oxide electrode material and its preparation method and its application in sodium ion battery
CN116143194B
Layered oxide positive electrode material of high-entropy sodium ion battery as well as preparation method and application of layered oxide positive electrode material
CN118472235A
Cited By
Method for synthesizing P2 / O3 composite phase sodium ion layered oxide
CN120573767A
Long-circulation high-capacity sodion layered oxide positive electrode material with low sodium-nickel mixed arrangement and preparation method and application of long-circulation high-capacity sodion layered oxide positive electrode material
CN121394380A